FRI0010 Prediction of radiographic progression in patients with rheumatoid arthritis by both magnetic resonance imaging and ultrasound. (12th June 2018) - Takatani, A.; Tamai, M.; Ohki, N.; Nakashima, Y.; Endou, Y.; Tsuji, S.; Shimizu, T.; Umeda, M.; Fukui, S.; Sumiyoshi, R.; Nishino, A.; Koga, T.; et al.
Abstract : Background: Magnetic resonance imaging (MRI) and ultrasound (US) are both useful modality to monitor disease status of RA whereas combination analysis of disease course by both modalities are quite few. Objectives: To clarify the predictors of radiographic progression in patients with RA examined by both MRI and US. Methods: Thirty-three patients with active RA, managed with a treat-to-target strategy and checked disease activity score every three months along with examination of both MRI and US, were enrolled from June 2010 to June 2016 and observed for 12 months. US of wrist and finger joints was examined every three months, MRI and radiograph were done every six months. US were evaluated by synovitis score of semi-quantitative manner by gray-scale (GS) and power Doppler (PD) proposed from EULAR. In MRI, synovitis, bone oedema and bone erosion were assessed by the Rheumatoid Arthritis Magnetic Resonance Imaging Scoring system (RAMRIS). Radiographic bone erosion and joint space narrowing (JSN) were scored by Genant-modified Sharp Score (GSS). Radiographic progression was defined as delta radiographic score >0.5. Multivariate analysis was employed to clarify independent predictors for radiographic progression at 12 month. Results: Thirteen patients were treated with methotrexate monotherapy and eighteen were received combination of methotrexate and biologics. Three were given biologic monotherapy. Median of age was 57.0 years and that of disease duration was 9 months. Female was 84.8%, positive rate of RF was 87.1% and that of ACPA was 79.3%. DAS28-CRP was 4.20, total GS score 6.0, total PD score 4.0, MRI synovitis score 6.0, MRI bone oedema score 3.0, MRI bone erosion score 3.0, and GSS score 1.0 at baseline. Radiographic progression was found in 12 patients. Multivariate analysis revealed that high MRI bone oedema score at baseline, high MRI bone oedema score and PD ≧ grade 2 articular synovitis at any joints at 6 month were associated with radiographic progression at 12 months. Clinical indices of DAS28-CRP at any point did not predict radiographic progression compared with MRI or US. Conclusions: During treat-to-target strategy, the presence of MRI bone oedema as well as PD ≧ grade 2 articular synovitis are found to be important to predict radiographic outcome in active RA patients. These imaging indices may be more sensitive to monitor radiographic progression as compared with clinical indices. Disclosure of Interest: None declared